2015
DOI: 10.1037/rep0000043
|View full text |Cite
|
Sign up to set email alerts
|

Perceived injustice after traumatic injury: Associations with pain, psychological distress, and quality of life outcomes 12 months after injury.

Abstract: This is the first study to examine perceived injustice in a trauma sample. Results support the presence of injustice perception in this group and its associations with pain and quality of life outcomes. Additional research is suggested to explore the impact of perceived injustice on recovery outcomes among individuals who have sustained traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 41 publications
12
89
2
2
Order By: Relevance
“…This result is consistent with previous studies in chronic pain showing that perceived injustice was associated with higher levels of disability and psychological distress [51,52]. This finding may be interpreted according to the Just World Theory [53], defined as the need for individuals to believe that they live in a world where people get what they deserve.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with previous studies in chronic pain showing that perceived injustice was associated with higher levels of disability and psychological distress [51,52]. This finding may be interpreted according to the Just World Theory [53], defined as the need for individuals to believe that they live in a world where people get what they deserve.…”
Section: Discussionsupporting
confidence: 82%
“…These findings suggested that evaluating perceived injustice may be warranted in future studies of outcomes following traumatic injury. Initial checks of internal consistency in Trost et al (2015) showed psychometric properties similar to those of previous studies; however, further validation of the IEQ in a heterogeneous trauma sample has yet to be formally conducted. Accordingly, the current study had two primary aims: 1) to validate the measurement model of the IEQ proposed by Sullivan et al (2008) and confirmed by Kennedy & Dunstan (2014) in a heterogeneous sample of patients admitted to a Level -1 trauma center, and 2) to test the reliability and validity of the IEQ in the same sample.…”
Section: Impactmentioning
confidence: 55%
“…Recruitment and study procedures are comprehensively described in Trost et al (2015). Study procedures were approved by the hospital's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research suggests that perceptions of injustice contribute to detrimental physical and psychological outcomes both among individuals with recent injury [43] and chronic pain conditions [13,26,31,38]. Pain-related injustice perception has been conceptualized as a cognitive appraisal reflecting the severity and irreparability of pain-or injury-related loss, externalized blame, and unfairness [37,38].…”
Section: Introductionmentioning
confidence: 99%